2013
DOI: 10.1002/pssc.201200457
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radiation damage on diffusion of fission products in silicon carbide

Abstract: The influence of irradiation induced damage on the transport of implanted species in poly and single crystalline silicon carbide is investigated. For this purpose published diffusion results of strontium, silver, iodine and cesium are compared with the associated evolution of defect profiles determined by α-particle channelling in a backscattering geometry. Strong diffusion takes place in the amorphized surface layer of room temperature implanted 6H-SiC during annealing at 1100 °C, which drops below the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
(26 reference statements)
2
22
0
Order By: Relevance
“…This lack of diffusion continued even after swift heavy ion bombardment annealing. In agreement with this, Friedland et al [102,134,135,286] also found that vacuum annealing at 1000°C resulted in no broadening (i.e. no diffusion) of the RBS peak of room temperature implanted iodine in 6H-SiC in commercially obtained CVD polycrystalline 3C-SiC.…”
Section: Iodine Diffusionmentioning
confidence: 52%
See 3 more Smart Citations
“…This lack of diffusion continued even after swift heavy ion bombardment annealing. In agreement with this, Friedland et al [102,134,135,286] also found that vacuum annealing at 1000°C resulted in no broadening (i.e. no diffusion) of the RBS peak of room temperature implanted iodine in 6H-SiC in commercially obtained CVD polycrystalline 3C-SiC.…”
Section: Iodine Diffusionmentioning
confidence: 52%
“…In contrast to the room temperature implanted samples, samples implanted at 600°C exhibited significantly less diffusion [102,134,286]. There was only diffusion in the initial stages of annealing due to defects introduced in the crystalline substrate during the ion bombardment process.…”
Section: Iodine Diffusionmentioning
confidence: 82%
See 2 more Smart Citations
“…measurements, where the diffusion of Cs in single crystalline (sc-SiC) 6H-SiC 8,9 and polycrystalline (pc-SiC) chemical vapor deposition (CVD)-SiC 8,9 were investigated using an ion implantation, followed by heating tests. These surrogate attempts can help understanding the release mechanism of FPs, however this method is known to create several complications.…”
Section: Introductionmentioning
confidence: 99%